Adherence to recommended electronic health record safety practices across eight health care organizations. (26th April 2018) - Sittig, Dean F; Salimi, Mandana; Aiyagari, Ranjit; Banas, Colin; Clay, Brian; Gibson, Kathryn A; Goel, Ashutosh; Hines, Robert; Longhurst, Christopher A; Mishra, Vimal; Sirajuddin, Anwar M; Satterly, Tyler; et al.
Abstract: Objective: The Safety Assurance Factors for EHR Resilience (SAFER) guides were released in 2014 to help health systems conduct proactive risk assessment of electronic health record (EHR)- safety related policies, processes, procedures, and configurations. The extent to which SAFER recommendations are followed is unknown. Methods: We conducted risk assessments of 8 organizations of varying size, complexity, EHR, and EHR adoption maturity. Each organization self-assessed adherence to all 140 unique SAFER recommendations contained within 9 guides (range 10–29 recommendations per guide). In each guide, recommendations were organized into 3 broad domains: "safe health IT" (total 45 recommendations); "using health IT safely" (total 80 recommendations); and "monitoring health IT" (total 15 recommendations). Results: The 8 sites fully implemented 25 of 140 (18%) SAFER recommendations. Mean number of "fully implemented" recommendations per guide ranged from 94% (System Interfaces—18 recommendations) to 63% (Clinical Communication—12 recommendations). Adherence was higher for "safe health IT" domain (82.1%) vs "using health IT safely" (72.5%) and "monitoring health IT" (67.3%). Conclusions: Despite availability of recommendations on how to improve use of EHRs, most recommendations were not fully implemented. New national policy initiatives are needed to stimulate implementation of these best practices.